2001
DOI: 10.1016/s0014-5793(01)02582-0
|View full text |Cite
|
Sign up to set email alerts
|

An NMR‐based metabonomic approach to the investigation of coelomic fluid biochemistry in earthworms under toxic stress

Abstract: The endogenous metabolites of the coelomic fluid of the earthworm Eisenia veneta were characterised using highresolution one-dimensional and two-dimensional 1 H nuclear magnetic resonance spectroscopy. Signals from common organic acids, such as acetate, fumarate, malonate, malate, formate, and succinate, were identified together with adenosine and nicotinamide mononucleotide. The potential use of this information as a baseline dataset for future toxicological or physiological studies was demonstrated by a meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
0
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(82 citation statements)
references
References 24 publications
3
76
0
1
Order By: Relevance
“…1A), which were 10-100 times intense than other metabolites. Malonate is a three-carbon dicarboxylic acid that can be found in diverse organism tissues including in the soybean tissues, rat brain, earthworm and mussel (Kim, 2002;Stumpf and Burris, 1981;Bundy et al, 2001). It is well known as a competitive inhibitor of cellular respiration since it binds to the active site of the succinate dehydrogenase in the tricarboxylic acid cycle.…”
Section: Discussionmentioning
confidence: 99%
“…1A), which were 10-100 times intense than other metabolites. Malonate is a three-carbon dicarboxylic acid that can be found in diverse organism tissues including in the soybean tissues, rat brain, earthworm and mussel (Kim, 2002;Stumpf and Burris, 1981;Bundy et al, 2001). It is well known as a competitive inhibitor of cellular respiration since it binds to the active site of the succinate dehydrogenase in the tricarboxylic acid cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Partial ecometabolomic studies allow the detection of the metabolic pathways affected by the pollution produced by different chemotoxic pollutants and also the key metabolites that improve the organism resistance both in plants (Trenkamp et al 2009;Kluender et al 2009) and in animals (Warne et al 2000;Bundy et al 2001;Viant et al 2006a, b;Samuelsson et al 2006;Bon et al 2006;Jones et al 2008a;Ekman et al 2008;Mckelvie et al 2009;Tuffnail et al 2009;Hansen et al 2010) (Table 1). For instance, Bundy et al (2002) have used ecometabolic fingerprinting NMR studies of the earthworm Eisenia veneta to ascertain initially the metabolites that changed their concentration when the worm was submitted to three different xenobiotics: 4-fluoroaniline, 3,5-difluoroaniline and 2-fluoro-4-methylaniline.…”
Section: Hypoxiamentioning
confidence: 99%
“…[10,11] Nuclear magnetic resonance (NMR)-based metabolomics offers a reliable, reproducible and high-throughput platform that is currently being utilised to study earthworm responses to sub-lethal exposure of contaminants in both contact and soil exposure tests. [1][2][3][12][13][14][15] Recent metabolomic studies with polycyclic aromatic hydrocarbons (PAHs) have suggested that the earthworm responses are concentration-dependent, but these studies did not assess whether or not the toxic MOA could be ascertained over a wide range of ultra-low sub-lethal concentrations. [12,16,17] For example, Brown et al [12] suggested that Eisenia fetida earthworm metabolic responses may be correlated with contaminant concentration but their study only included three different exposure concentrations and did not clearly identify the MOA.…”
Section: Introductionmentioning
confidence: 99%